MIGRATION CRISIS AND NEW OPPORTUNITIES FOR TURKEY - N. M. Mikheeva (Vestnik MGIMO-Universiteta)
The article discusses some aspects of the relationship of the European Union and Turkey. Against the backdrop of the immigration crisis, that has gripped almost all countries in Europe, the EU states were forced to appeal to the Turkish Government for assistance. Europe requested to withhold part of the f refugees on the territory of Turkey. The EU promised financial support. The Government of RecepTayyip Erdogan linked problems with the issue of refugees entering the country in the EU. The author analyzes the possibility of positive promotion of the negotiation process on Turkey's EU membership. Focuses on the settlement of the Cyprus problem, as one of the three major political obstacles to Turkey in Europe. We are seeing a situation in which EU political circles are willing to exert pressure on the Cyprus conflict and to push for the signing of a formal treaty on the settlement of problem. Some progress in the negotiation process between the communities of Cyprus EU starts to participate in the negotiations on Cyprus, together with the United Nations. Creates good conditions for the settlement of the conflict. Such a way of resolving the long-standing territorial-community conflict creates much more new problems on the island. Obstacles to the integration of Turkey into the EU will become even more.